Structure sensitivity of parameters of acoustic relaxation а-peak in niobium and iron - Natsik, V.D.; Pal-Val, P.P.; Pal-Val, L.N.; Semerenko, Yu.A. (Functional Materials, 2004)
Influence of dislocation structure on parameters of low-temperature internal friction а-peak and related Young’s modulus defect has been studied in niobium single crystals and polycrystals and pure iron single crystals. A statistical interpretation of the temperature dependence and structure sensitivity of dynamic relaxation characteristics in the vicinity of а-peak has been proposed based on assumed random scatter of activation energy of elementary relaxators. The attempt period, average value, and dispersion of activation energy have been estimated for the relaxation process responsible for the а-peak in the materials studied. Ha моно- и поликристаллах ниобия с различной концентрацией примесей, а также на монокристаллах чистого железа экспериментально изучено влияние изменения дислокационной структуры образцов на параметры низкотемпературного а-пика внутреннего трения и соответствующего ему дефекта модуля Юнга. Предложена статистическая интерпретация температурной зависимости и структурной чувствительности характеристик динамической релаксации в окрестности а-пика, основанная на предположении о случайном разбросе значений энергии активации элементарных релаксаторов. Получены эмпирические оценки для периода попыток, среднего значения и дисперсии энергии активации релаксационного процесса, ответственного за а-пик в изученных материалах. На моно- та полікристалах ніо6ію з різним вмістом домішок, а також на монокристалах чистого заліза експериментально вивчено вплив зміни дислокаційної структури зразків на параметри низькотемпературного a-піку внутрішнього тертя та відповідного йому дефекту модуля Юнга. Запропоновано статистичну інтерпретацію температурної залежності та структурної чутливості характеристик динамічної релаксації в області a-піку, яка базується на припущенні про наявність випадкового розкиду значень енергії активації елементарних релаксаторів. Отримано емпіричні оцінки для періоду спроб, середнього значення та дисперсії енергії активації релаксаційного процесу, що відповідає за a-пік у вивчених матеріалах.